2020
DOI: 10.3390/tropicalmed5040160
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Knowledge and Practices among Domestic Hajj Pilgrims: Implications for Future Mass Gatherings Amidst COVID-19

Abstract: This study examined Hajj pilgrims’ knowledge and reported practice of hand hygiene. In Hajj 2019, a cross-sectional survey was undertaken in Mina, Makkah, Saudi Arabia, of domestic Saudi pilgrims aged ≥18 years by using a self-administered Arabic questionnaire that captured data on pilgrims’ socio-demographics, hand hygiene knowledge, and reported practices of hand cleaning following certain actions. A total of 348 respondents aged 18 to 63 (median 32) years completed the survey, of whom 200 (57.5%) were femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 23 publications
2
14
1
Order By: Relevance
“…When participants were asked about their hand hygiene practices at specific high-risk situations, soap and water was the most preferred method reportedly used, followed by alcohol-based hand rubs. This finding is in parallel with the results of formerly conducted studies among attendees of Hajj and Umrah pilgrimage that found hand washing with soap and water was more prevalent than other hand hygiene methods [ 15 , 26 , 27 , 28 ]. It is also noteworthy that Saudi Arabian citizens have a preference for using soap and water to ABHR as a preventive measure against COVID-19 [ 19 ].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…When participants were asked about their hand hygiene practices at specific high-risk situations, soap and water was the most preferred method reportedly used, followed by alcohol-based hand rubs. This finding is in parallel with the results of formerly conducted studies among attendees of Hajj and Umrah pilgrimage that found hand washing with soap and water was more prevalent than other hand hygiene methods [ 15 , 26 , 27 , 28 ]. It is also noteworthy that Saudi Arabian citizens have a preference for using soap and water to ABHR as a preventive measure against COVID-19 [ 19 ].…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, approximately 27% of the Saudi Arabian citizens did not wash their hands after nose-blowing, coughing, or sneezing amidst the COVID-19 pandemic [ 17 ]. Conversely, hand hygiene compliance in this study improved slightly following other high-risk actions, e.g., about 98% of visitors of the mosque cleaned their hands after touching a patient and 99% cleaned hands following waste disposal, whereas 85% and 90% of pilgrims, respectively, during the 2019 Hajj complied [ 15 ]. Another survey involving Umrah pilgrims conducted in 2019 showed that over 90% of pilgrims washed their hands with soap and water or sanitisers after coughing and sneezing, before eating or preparing food, and after using the bathroom [ 29 ].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations